2006
DOI: 10.1128/aem.02429-05
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Significance of Phage Attack on Starter Cultures: a Mechanistic Model for Population Dynamics of Phage and Their Hosts Isolated from Fermenting Sauerkraut

Abstract: We investigated the possibility of using starter cultures in sauerkraut fermentation and thereby reducing the quantity of salt used in the process. This, in turn, would reduce the amount of waste salt that would enter in our water resources. Phage, naturally present in sauerkraut fermentation, could potentially affect the starter cultures introduced. Thus, a mechanistic mathematical model was developed to quantify the growth kinetics of the phage and starter cultures. The model was validated by independent exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
0
13
1
Order By: Relevance
“…Previous studies have reported that the fermentation temperature and acidity are important determinants of the microbial community composition in kimchi fermentation (5,27). However, our results showed that in addition to temperature and acidity, a new influence, that of bacteriophages, was another clearly important determinant of microbial community dynamics, as in sauerkraut fermentation (31,32,37), especially at the end stages of kimchi fermentation.…”
Section: Statistics Of Sequences Generated By 454 Pyrosequencingcontrasting
confidence: 54%
“…Previous studies have reported that the fermentation temperature and acidity are important determinants of the microbial community composition in kimchi fermentation (5,27). However, our results showed that in addition to temperature and acidity, a new influence, that of bacteriophages, was another clearly important determinant of microbial community dynamics, as in sauerkraut fermentation (31,32,37), especially at the end stages of kimchi fermentation.…”
Section: Statistics Of Sequences Generated By 454 Pyrosequencingcontrasting
confidence: 54%
“…The average burst size of ⌽1-A4 is 24 particles per infective center. The latency period is about 30 min in MRS broth supplemented with 10 mM CaCl 2 at 30°C based on a one-step growth kinetics curve (56). In addition to infecting its natural host, L. mesenteroides 1-A4, ⌽1-A4 was also found to infect two other L. mesenteroides strains, 1-B8 and 1-E10 (48).…”
Section: Resultsmentioning
confidence: 95%
“…Recent studies have shown that phages are present in the vegetable fermentations (4,47,48,74,75). Because of the rapid lytic cycle of these phages, they may significantly impact starter cultures and bacterial succession in vegetable fermentations (56). Phages active against L. mesenteroides have been isolated and characterized (48); however, genome sequences have not been reported.…”
mentioning
confidence: 99%
“…Bacteriophages are able to selectively infect and kill susceptible bacteria, in the process producing large numbers of progeny that are similarly capable and therefore have considerable potential for use as self-replicating pharmaceuticals (21). It has been argued that threshold phenomena determine the success and mode of action of phage therapies (11,(21)(22)(23)29), and the predictions of various pharmacokinetic and pharmacodynamic (PK/PD) models have been tested against in vitro data for a variety of bacterial species (2,11,16,17,24,28). These models are broadly consistent with phage-bacterium interactions observed experimentally, but they do not address the issue of how to prevent or alleviate the possible emergence of phage-resistant bacteria.…”
mentioning
confidence: 99%